Sensing and warning-based technology applications to improve occupational health and safety in the construction industry: A literature review. Issue 8 (10th May 2019) - Antwi-Afari, Maxwell Fordjour; Li, Heng; Wong, Johnny Kwok-Wai; Oladinrin, Olugbenga Timo; Ge, Janet Xin; Seo, JoonOh; Wong, Arnold Yu Lok
Abstract : Purpose: Sensing- and warning-based technologies are widely used in the construction industry for occupational health and safety (OHS) monitoring and management. A comprehensive understanding of the different types and specific research topics related to the application of sensing- and warning-based technologies is essential to improve OHS in the construction industry. The purpose of this paper is to examine the current trends, different types and research topics related to the applications of sensing- and warning-based technology for improving OHS through the analysis of articles published between 1996 and 2017 (years inclusive). Design/methodology/approach: A standardized three-step screening and data extraction method was used. A total of 87 articles met the inclusion criteria. Findings: The annual publication trends and relative contributions of individual journals were discussed. Additionally, this review discusses the current trends of different types of sensing- and warning-based technology applications for improving OHS in the industry, six relevant research topics, four major research gaps and future research directions. Originality/value: Overall, this review may serve as a spur for researchers and practitioners to extend sensing- and warning-based technology applications to improve OHS in the construction industry.